2022
DOI: 10.1212/wnl.0000000000013148
|View full text |Cite
|
Sign up to set email alerts
|

Age-Stratified Risk of Cerebral Venous Sinus Thrombosis After SARS-CoV-2 Vaccination

Abstract: Background and ObjectivesCerebral Venous Sinus Thrombosis (CVST) as a part of the thrombosis and thrombocytopenia syndrome is a rare adverse drug reaction of SARS-CoV-2 vaccination. Estimated background rate of CVST with thrombocytopenia is 0.1 per million per month. We assessed the age-stratified risk of CVST with and without thrombocytopenia after SARS-CoV-2 vaccination.MethodsWe estimated the absolute risk of CVST with and without thrombocytopenia within 28 days of first dose of four SARS-CoV-2 vaccinations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…1 Two adenovirus-based COVID-19 vaccinations have been associated with a rare risk of simultaneous acute thrombosis-usually cerebral venous sinus thrombosis (CVST)-and thrombocytopenia in an entity called vaccine-induced thrombotic thrombocytopenia. 2,3 CVST is rare in the non-COVID general population. Risk factors for CVST include pregnancy, malignancy, hormone use, and thrombophilia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Two adenovirus-based COVID-19 vaccinations have been associated with a rare risk of simultaneous acute thrombosis-usually cerebral venous sinus thrombosis (CVST)-and thrombocytopenia in an entity called vaccine-induced thrombotic thrombocytopenia. 2,3 CVST is rare in the non-COVID general population. Risk factors for CVST include pregnancy, malignancy, hormone use, and thrombophilia.…”
mentioning
confidence: 99%
“…Two adenovirus-based COVID-19 vaccinations have been associated with a rare risk of simultaneous acute thrombosis—usually cerebral venous sinus thrombosis (CVST)—and thrombocytopenia in an entity called vaccine-induced thrombotic thrombocytopenia. 2,3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The absolute risk of VITT and VITTrelated CVT is estimated at 20 and 8 per million first doses of ChAdOx1 nCoV-19, respectively. 5,6 So far, no definite VITT cases occurring after a second ChAdOx1 nCoV-19 vaccine dose have been reported, raising the question if VITT only occurs after a first dose. Two pharmacovigilance studies reported cases of thrombosis with thrombocytopenia after a second ChAdOx1 nCoV-19 dose, but because of lack of clinical data, none of these could be classified as VITT.…”
mentioning
confidence: 99%
“…Nevertheless, it is still one of the largest studies on this extremely rare disease, for which power calculations and an interventional randomized study is not feasible. 24 Although true consecutiveness of cases in all countries participating in the registry remains a challenge, we attempted to minimize this bias ensuring inclusion of consecutive patients from the participating centers. Furthermore, complex patterns of management of patients with VITT‐CVT led to the presence of confounders which were difficult to account for and make the results vulnerable to confounding by indication.…”
Section: Discussionmentioning
confidence: 99%